Development Of Integrative Food Waste Treatment And Lactic Acid Production - Nursyafawati, Bakhari (2022)
Food waste has disposed in landfills and has been caused to greenhouse gas emissions, foul odors, poisonous leaching and flea attraction as well as filling a potential land area. In Malaysia, the production of waste amount to 45 % which 17,000 tonnes of food waste was collected each years and estimated increased to 3.18 million tonnes in 2022. Related to this research, the objective has been achieved were to perform validation test on treatment process of food waste and to develop lactic acid production from food waste using fermentation process. According to the rising amount of food waste production and damaging effects, the better way to managing this organic waste is being introduced. In this research, fermentation process has been used as a treatment process to recycle the food waste to achieve the objective. There are two types of food waste has been used for this research namely agriculture waste and domestic waste. All the food waste has grinded separately in 1L water with 500 g of food waste into form of food waste slurry (including sterilization), initial pH adjusted to pH 7 and fermented statically at room temperature 28°C. Moreover, the parameters of food waste have been measured before and after fermentation process to know the sample control and the fraction of food waste that can produce the highest yield was determined. Also food waste efficiency, in term of producing the final product which is lactic acid also has been studied. In addition, the most efficient food waste on produce the high yield of food waste treatment to lactic acid is domestic waste. About 60 - 70% of food waste treatment has been achieved when 100 percent ratio of vitagen used as inoculum was added into food waste sample 1 and 2 for fermentation (treatment process). The results showed that the efficiency of food waste treatment using fermentation process not only can produce high yield of food treatment process, also can enhanced lactic acid production.